Beasts of Abigaile. vol. 3 - Spica, Aoki (Seven Seas Entertainment, 2018)
Nina's perfume has been stolen! Without it, she doesn't have a way to disguise her true human nature, and there's nothing lugas hate more than humans. If she can prove she is not like the other humans, Roy promises to give her perfume back-but if she fails, he'll kill her! --Provided by Publisher.